Bureaucrats in business (New York, 1995)
Despite more than a decade of privatization, state-owned enterprises account for nearly as large a share of developing countries' economies today as twenty years ago. Often inefficient government firms and the resulting deficits hinder growth, making it harder for people to escape poverty.Bureaucrats in Business shows how divestiture and other reforms can improve the economy, why politics often impedes reform, and how countries that reformed successfully overcame these obstacles.
Keywords: World bank policy research report